2002
DOI: 10.1021/jp0155967
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Spin-State Preference by Substituents:  A Case Study of Thianthrene Dication

Abstract: We report an effective example of π-conjugated systems showing the reverse spin-state preferences depending on the substitution patterns. It is shown that 2,3,7,8-and 1,4,6,9-tetramethoxy-substituted thianthrenes have different electronic structures owing to destabilization of the specific frontier molecular orbitals. On the basis of the hybrid Hartree-Fock/density functional method (B3LYP/6-31G*), the singlet-triplet energy gaps are estimated to be -10.7 and +8.8 kcal/mol for 2,3,7,8-and 1,4,6,9-substituted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Gas-phase calculations on TH predict a ground-state geometry of butterfly shape with a folding angle around the S-S axis (see Figure 1 for a definition) of ∼129°, in good agreement with a recent X-ray structure. [25][26][27]69 However, in benzene solution and in an ordering liquid (Merck Nematic Phase IV) folding angles of ∼140°have been reported. 70,71 Our results in the liquid, shown in the upper panel of Figure 6, are consistent with this shift to larger angles.…”
Section: Structure Of Tetrathiafulvalene and Thianthrene In Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas-phase calculations on TH predict a ground-state geometry of butterfly shape with a folding angle around the S-S axis (see Figure 1 for a definition) of ∼129°, in good agreement with a recent X-ray structure. [25][26][27]69 However, in benzene solution and in an ordering liquid (Merck Nematic Phase IV) folding angles of ∼140°have been reported. 70,71 Our results in the liquid, shown in the upper panel of Figure 6, are consistent with this shift to larger angles.…”
Section: Structure Of Tetrathiafulvalene and Thianthrene In Solutionmentioning
confidence: 99%
“…24 Additionally, its butterfly shape (Figure 1) has triggered a number of theoretical investigations. [25][26][27] MeCN is a commonly employed aprotic solvent that has not yet been characterized by ab initio molecular dynamics simulation. In the context of electron-transfer reactions, it is noteworthy that MeCN is a typical solvent in dye-sensitized solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of substituents on the singlet-triplet gaps in diradicals has been studied by many theoretical and experimental groups. [6][7][8][9][10][11][12][13][14] For example, for a 1,4-didehydrobenzene diradical, Clark and Davidson 6 found that substituents, which strongly interact with the benzyne system, do not interact with the space, and are only weakly electronegative, should yield the smallest singlet-triplet energy differences and might lead to the triplet ground state. Berson and co-workers 8,9 reported that electron-withdrawing substituents modulate the singlet-triplet gaps of the singlet tetramethyleneethane-type diradical.…”
Section: Introductionmentioning
confidence: 99%
“…Berson and co-workers 8,9 reported that electron-withdrawing substituents modulate the singlet-triplet gaps of the singlet tetramethyleneethane-type diradical. Ito et al 10 reported examples of -conjugated trianthrene systems showing the reverse spin-state preferences depending on the substitution patterns. Geise and Hadad 11 found that for ortho-, meta-, and para-substituted phenylcarbenes aromatic ring substituents have a large effect on the singlet-triplet splitting.…”
Section: Introductionmentioning
confidence: 99%
“…1) and the bilateral benzene rings have no electronic interaction with each other in the neutral state, while the two-electron oxidation of THA gives the closed-shell dication of THA (THA 2+ ) with a planar 14p aromatic system similar to anthracene. [15][16][17] Bisanthra-thianthrene (BA-THA) is a larger family of THA. The investigation of oxidation behavior of BA-THA is important for understanding the fundamental properties of dithiaacenes.…”
mentioning
confidence: 99%